Kajian Kerusakan Bangunan Sederhana Pasca Gempa Banjarnegara 18 April 2018 - Elvis Saputra; Restu Faizah (Universitas Muhammadiyah Surabaya, 2019)
AbstractThe 4.4 SR earthquake occurred in Banjarnegara Regency, especially Kalibening subdistrict, on Wednesday, April 18, 2018. Although it has not high magnitude, the structural damage was severe. There were 201 units of structural damage in term of medium to large. It generates the question from stakeholders, what cause of the structural damage. Therefore, this study visited the affected areas of Banjarnegara Earthquake to investigate the causative factor of structural damage, especially for a simple structure which is residential houses, schools and mosque buildings. The study found some causative factors of structural damages. The first is the depth of the earthquake source that is quite shallow i.e. 4 km. The second is the quality of simple buildings that were damaged or collapsed in the affected area might do not have a good quality and do not qualify for earthquake resistant buildings. The sample of cases found in the field is the structural systems that have not good integrated and good material. Besides that, It was found a community innovation to reduce building costs but they did not have the correct method. An example is the use of bamboo as a substitute for steel reinforcements in the frame. Based on this study, the further research into the bamboo usage guidelines as a substitute for steel reinforcement should be carried out and socialized.Keywords: Earthquake, structural demage, causative factor. AbstrakRabu 18 April 2018 Kabupaten Banjarnagara tepatnya di Kecamatan Kalibening dilanda gempabumi dengan kekuatan 4,4 SR, meskipun magnitud gempa tidak terlalu besar namun kerusakan bangunan yang di timbulkan cukup banyak, tercatat dampak yang ditimbulkan oleh gempa sebanyak 201 bangunan mengalami kerusakan mulai dari rusak sedang hingga rusak berat. Fakotr penyebab banyaknya bangunan yang mengalami kerusakan adalah karena memiliki kedalaman pusat gempa yang cukup dangkal, yaitu 4 Km menyebabkan intensitas guncangan di purmakaan tanah terasa cukup kuat. Selain dari faktor kedalaman pusat gempa, banyaknya bangunan rumah, sekolah dan masjid yang rusak atau roboh disebabkan karena tidak mengikuti kaidah-kaidah bangunan tahan gempa. Contoh kasus yang ditemukan di lapangan seperti sistem struktur yang kurang menyatu dan kualitas material yang kurang baik. Dilokasi kerusakan ditemukannya inovasi-inovasi masyarakat dalam menekan biaya bangunan seperti pengunaan bambu sebagai pengganti tulangan baja dan ada juga yang mengkombinasikan dalam satu frame struktur menggunakan tulangan bambu dan tulangan baja, namun penerapan bambu sebagai pengganti tulangan oleh masyarakat tidak dibuat dengan praktek yang semestinya. Kata Kunci: Gempa, Kerusakan bangunan, Faktor penyebab.